Examination of economic convergence of the Slovak Republic - Jankalová, Miriam; Jankal, Radoslav (Business: Theory and Practice, 2008)
The convergence criteria about the entry of the country into the Eurozone expressly predicate “only” of thetemporary competence to conform the monetary and fiscal policies to the requirements of the current Eurozone members.The convergence criteria do not indicate the readiness rate of economics subjects and conditions for Eurozone and do notpredicate about the functionality of Eurozone also. It is understandable, to a certain extent, from the view of currentmembers of Economic and Monetary Union, that they test the “candidates”, if they do not cause the financial problemsto them. Article in German. Prüfung der Wirtschaftlichen Konvergenzder Slowakischen Republik Auszug. Die Konvergenzkriterien über den Eintritt des Landes in die Eurozone sprechen deutlich “nur” über vorübergehendeFähigkeit die monetäre Politik und Fiskalpolitik den Forderungen jeweiliger Mitglieder der Eurozone anzupassen. Nämlich dieKonvergenzkriterin deuten nicht auf die Vorbereitung der wirtschaftlichen Subjekten, die Bedingungen in der Eurozone, wiesoauch auf die Funktionalität der Eurozone hin. Aus Sicht jeweiliger Mitglieder der Wirtschafts- und Währungsunion ist esdurchaus verständlich, “Bewerber” zu bewerten, um keine Finanzprobleme zu entdecken. Schlüsselwörter: Konvergenzkriterien, Europäische Union, Eurozone, Währungsunion, Stabilität, Business, Management and Economics Engineering. First published online: 19 Mar 2008